2018
DOI: 10.1136/thoraxjnl-2017-211090
|View full text |Cite
|
Sign up to set email alerts
|

Stability of ARDS subphenotypes over time in two randomised controlled trials

Abstract: ARDS subphenotypes are largely stable over the first 3 days of enrolment in two ARDS Network trials, suggesting that subphenotype identification may be feasible in the context of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 21 publications
(26 reference statements)
1
98
0
Order By: Relevance
“…It is tempting to speculate that virus-associated CRS and the neutrophilic response are the main culprits in severe COVID-19-pneumonia, which occurs with a delay only when the "misguided antiviral-immune response" hits 23 . One might argue, that ARDS per se implies alveolar endothelial injury, complement-, neutrophil-activation, and NETosis and thus entails a systemic hyperin ammatory response [32][33][34] . Still, others have reported, that an increased NLR is apparent already before the onset of ARDS, and was an independent predictor for severe COVID-19 in 61 patients 31,35 .…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that virus-associated CRS and the neutrophilic response are the main culprits in severe COVID-19-pneumonia, which occurs with a delay only when the "misguided antiviral-immune response" hits 23 . One might argue, that ARDS per se implies alveolar endothelial injury, complement-, neutrophil-activation, and NETosis and thus entails a systemic hyperin ammatory response [32][33][34] . Still, others have reported, that an increased NLR is apparent already before the onset of ARDS, and was an independent predictor for severe COVID-19 in 61 patients 31,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a high PEEP strategy was associated with a significant decrease in mortality in the hyperinflammatory group suggesting a possible therapeutic implication of distinguishing phenotypes [8] . These two types persisted over time with > 94% of patients remaining within their initial phenotype by hospital day three [46] . A follow up study with 2 distinct cohorts demonstrated increased levels of markers of epithelial cell injury with decreased levels of markers of endothelial injury in direct ARDS (defined as those with pulmonary cause such as pneumonia) compared with indirect ARDS (caused by non-pulmonary etiologies such as sepsis) [47] .…”
Section: Cytokines In Ardsmentioning
confidence: 98%
“…[810] The subgroups are clinically and biologically distinct from one another and remain stable over the first three days of enrollment. [11] The hyper-inflammatory subphenotype was associated with increased inflammatory biomarkers, a higher prevalence of shock, and worse clinical outcomes. Crucially, in the hyper-inflammatory subphenotype, we observed treatment responses to positive end-expiratory pressure (PEEP) and conservative fluid management that were significantly different from the hypo-inflammatory class.…”
Section: Introductionmentioning
confidence: 99%